Teaching law : justice, politics, and the demands of professionalism - West, Robin, 1954- (New York, NY : Cambridge University Press, 2014)
'Teaching Law reimagines law-school teaching and scholarship by going beyond crises now besetting the legal academy and examining deeper and longer-lasting challenges. The book argues that the legal academy has long neglected the needs to focus teaching and scholarship on the ideals of justice that law fitfully serves, the political origins of law, and the development of a respectful but critical relationship with the legal profession. This book suggests reforms to improve the quality of legal education and responds to concerns that law schools eschew the study of justice, rendering students amoralist; that law schools slight the political sources of law, particularly in legislative action; and that law schools have ignored the profession entirely. These areas of neglect have impoverished legal teaching and scholarship as the academy is refashioned in response to current financial exigencies, and addressing them is long overdue'--
Introduction: the trouble with law schools -- The unbearable lightness of justice -- Politics and its discontents -- The bifurcated academy: the practice versus the study of law -- Confronting our existential challenge -- Some conclusions.
Includes bibliographical references (pages 217-236) and index.
Keywords: Law -- Study and teaching -- United States; Law schools -- United States